It Is Advisable to Control the Duration of Hypothermia Circulatory Arrest During Aortic Dissection Surgery: Single-Center Experience - Song, Jian; Wu, Jinlin; Sun, Xiaogang; Qian, Xiangyang; Wei, Bo; Wang, Wei; Wang, De; Qiu, Jiawei; Cao, Fangfang; Gao, Wei; Zhao, Rui; Dai, Lu; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: The duration of hypothermia circulatory arrest (HCA) is one of the important factors affecting the prognosis of arch surgery, and which is still controversial. The purpose of this study was to investigate the effect of HCA duration on early prognosis in Type A aortic dissection (TAAD) patients who underwent arch surgery in our center. Methods: All consecutive patients who underwent surgical treatment for TAAD in Fuwai Hospital from January 2010 to December 2018 were included in this study and divided into four quartile groups based on HCA time. Baseline characteristics, perioperative indicators and early mortality were statistically analyzed by propensity score matching (PSM) and restricted cubic spline (RCS) method. Perioperative adverse events were confirmed according to the American STS database and Penn classification. Results: 1018 consecutive patients (mean age 49.1±11.4 years, male 74.7%) with TAAD treated surgically were eventually included in the study. After PSM, with the prolongation of HCA time, the surgical mortality rate of group [2,15], (15,18], (18,22] and (22,73] were 4.1%, 6.6%, 7.8% and 10.9% with p=.041, respectively. As shown in RCS, the mortality rate increased sharply after the HCA time exceeded 22 minutes. And from the subgroup analysis, the HCA time of 22 minutes or less was associated with better clinical outcomes (OR 2.09, 95%CI 1.25-3.45, p=.004). Conclusions: The early mortality increases significantly with the duration of HCA time when arch surgery performed. And multiple systems throughout the body can be adversely affected.